Cryogenic Treatment Effect on the Wear Resistance of AM60 Magnesium Alloy - B. Gassama; B. Karahisar; N. Öztürk Körpe; M.Ö. Öteyaka (Archives of Metallurgy and Materials)
Magnesium alloys were used as structural materials due to their low density. However, the poor wear behavior of magnesium alloys limits their use. In this study, AM60 magnesium alloy was subjected to deep cryogenic heat treatment to enhance the wear properties in dry and wet conditions with different loads. For this purpose, a deep cryogenic treatment at –196°C was applied for 48 h to the AM60 magnesium alloy. On the other hand, the wear performance of the treated sample was compared to the untreated sample using the pin-on-disc method at loads of 1 N, 2 N, and 3 N. The microstructure and wear groove were investigated using imaging techniques, while the XRD method characterized the phase modification. The results showed that the microstructures of the untreated sample drastically changed; the eutectic phase around the β phase was dissolved in the matrix, and some twins were formed after heat treatment. The XRD analysis confirmed the formation of a new β phase belonging to twins and an increase of the current β phase. Regarding hardness behavior, it increased by ~17.5% compared to the untreated sample after cryogenic treatment. In dry conditions, abrasive wear was the primary mechanism, and the wear resistance was better for the treated sample for all loads applied due to probably new phase formation. The treated sample exhibited lower wear resistance against the untreated sample, apparently due to the oxidative wear mechanism.